A mannose 6-phosphate-containing N-linked glycopeptide derived from lysosomal acid lipase is bound to MHC class II in B lymphoblastoid cell lines. - Dustin, M; McCourt, D; Kornfeld, S (1996)
Binding of peptides to MHC class II Ag generates ligands for TCR of Th lymphocytes. We have identified a novel class of peptides bound to MHC class II: mannose 6- phosphate (Man-6-P) containing glycopeptides from lysosomal enzymes. These species were identified in the process of characterizing mannose 6-phosphate/insulin-like growth factor II (M-6-P/IGF-II) receptor binding to the surface of B lymphoblasts. Surface iodination and Man-6-P/IGF-II receptor affinity chromatography implicated MHC class II as a carrier of Man-6-P-modified oligosaccharides. These oligosaccharides were found to be primarily associated with the bound peptide. Peptides eluted from the Man-6-P/IGF-II receptor-binding fraction of immunoaffinity-purified MHC class II from the Swei cell line contained a sequence derived from the propiece of lysosomal acid lipase. Partial sequences were also obtained for peptides from other HLA-DR alleles but none of these were attributable to known proteins. This study defines a novel approach for isolating rare glycan-modified peptides from MHC class II and demonstrates that very large secondary modifications are tolerated in peptides bound to MHC class II.